2022
DOI: 10.1002/anie.202208016
|View full text |Cite
|
Sign up to set email alerts
|

Direct Dry Synthesis of Supported Bimetallic Catalysts: A Study on Comminution and Alloying of Metal Nanoparticles

Abstract: Ball milling is growing increasingly important as an alternative synthetic tool to prepare catalytic materials. It was recently observed that supported metal catalysts could be directly obtained upon ball milling from the coarse powders of metal and oxide support. Moreover, when two compatible metal sources are simultaneously subjected to the mechanochemical treatment, bimetallic nanoparticles are obtained. A systematic investigation was extended to different metals and supports to understand better the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, given favorable mixing conditions, it has been observed that when hard and soft, brittle and plastic samples are processed together, the harder component can act as a grinding body toward the soft and plastic one, and thus subject it to activation by means of deformation, which will lead to the latter being smeared over the former . These processes probably are the phenomenological reason for the successful mechanochemically induced deposition of metal nanoparticles (soft) over oxide supports (hard), in addition to the intrinsic metal–support interactions. , At the same time, such a notion could explain why attempts to extend the method to the synthesis of carbon-supported metal nanoparticles had failed so far, at least when coarse metal powders (soft) were combined with a suitable carbon source (soft) under seemingly suitable conditions . Thus, in this study, metal acetylacetonate salts were selected as the metal precursors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given favorable mixing conditions, it has been observed that when hard and soft, brittle and plastic samples are processed together, the harder component can act as a grinding body toward the soft and plastic one, and thus subject it to activation by means of deformation, which will lead to the latter being smeared over the former . These processes probably are the phenomenological reason for the successful mechanochemically induced deposition of metal nanoparticles (soft) over oxide supports (hard), in addition to the intrinsic metal–support interactions. , At the same time, such a notion could explain why attempts to extend the method to the synthesis of carbon-supported metal nanoparticles had failed so far, at least when coarse metal powders (soft) were combined with a suitable carbon source (soft) under seemingly suitable conditions . Thus, in this study, metal acetylacetonate salts were selected as the metal precursors.…”
Section: Resultsmentioning
confidence: 99%
“…20 These processes probably are the phenomenological reason for the successful mechanochemically induced deposition of metal nanoparticles (soft) over oxide supports (hard), in addition to the intrinsic metal−support interactions. 17,19 At the same time, such a notion could explain why attempts to extend the method to the synthesis of carbon-supported metal nanoparticles had failed so far, at least when coarse metal powders (soft) were combined with a suitable carbon source (soft) under seemingly suitable conditions. 21 Thus, in this study, metal acetylacetonate salts were selected as the metal precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The method proved to be somewhat flexible concerning the choice of metals and oxide support. 30 In fact, compatibly with the scope of the study, it was used to prepare a variety of supported PdAg catalysts with different relative content of Pd and Ag. The effect of composition on catalytic behavior was studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Various kinds of catalytic materials, including metal particles, supported metal and bimetallic catalysts, metal oxides, and metal-organic frameworks, have been synthesized by mechanochemistry. [5][6][7][8][9] The synthetic method endows the materials with a unique nature, such as an increase in the surface area, change of chemical composition, and alteration of the structure, which usually are impossible to achieve by traditional strategies. Recently, Amol P. Amrute et al synthesized nanometer-sized α-Al 2 O 3 with a surface area up to 140 m 2 g −1 by a mechanochemical method at room temperature.…”
Section: Introductionmentioning
confidence: 99%